Weight Patterns of Youth Entering an Urban Juvenile Justice Facility. (January 2015) - Keough, Lori; Beckman, Dawn; Sinclair, Tatum; Young, Shannah; Baichoo, Shelanda; Cobb, Meghan
Adolescents with a history of incarceration face a disproportionate number of health issues compared with their peers in virtually all areas, including perceived well-being; self-esteem; acute, chronic, and psychosocial disorders; and physical activity. Some studies have shown correlates of weight status and incarceration; however, the literature is conflicting. The current study sought to assess weight patterns of primarily minority urban youth ( N = 548) entering a juvenile justice facility as well as associations between medications and weight status. Results indicate incarcerated adolescents have higher rates of overweight and obesity (40%) in comparison with nonincarcerated adolescents in the state (20 to 30%) or surrounding community (30 to 34%). Of interest, incarcerated adolescents taking asthma medications have significantly higher rates of overweight and obesity when compared with those not taking asthma medications. The clinical implications of these findings are discussed and implications for future research explored.